Substrate-dependent lipid and β-carotene production in engineered Yarrowia lipolytica: a comparative study - Raúl Robles-Iglesias; Jean-Marc Nicaud; María C. Veiga; Christian Kennes (AMB Express)
Abstract This study evaluates the influence of various substrates (glucose, glycerol, and acetic acid) on the growth and metabolite production of Yarrowia lipolytica in fed-batch bioreactors. The primary aim is to understand how substrate choice impacts lipid and β-carotene production, critical for bioenergy and bioproducts. The study demonstrates that the choice of substrate significantly influences biomass yield, lipid content, and β-carotene levels. Among the substrates tested, glycerol yielded the highest biomass concentration of 5.31 g/L. Glucose led to the highest lipid content, with a yield of 35.8% (g lipids/g biomass), while acetic acid resulted in the highest lipid concentration, reaching 1.42 g/L. In terms of β-carotene production, glucose showed the highest content per cell at 63.3 mg/g, whereas glycerol led to the highest overall concentration of 202 mg/L. These findings highlight Y. lipolytica’s versatility and potential as a flexible platform to produce lipids and β-carotene, which are essential for developing sustainable biofuels and bioproducts. The study underscores the significant variations in metabolite production based on substrate choice, emphasizing on the importance of tailored strategies to optimize industrial applications. Further research may explore optimizing fermentation conditions to enhance production yields, making this yeast a viable option for various biotechnological applications.